(Moroccan) Mixed Arabic in digital media: A comparative analysis of oral and written practices in Moroccan digital platforms and newspapers - Pennisi, Rosa (Lingua Posnaniensis, 2026)
This study aims to analyze the transition of (Moroccan) Mixed Arabic from oral to written productions in digital communication. The phenomenon of literacy in written Moroccan Arabic is an issue already observed by scholars, especially concerning the developments of standardization from below (Caubet 2017a-b, 2018; Miller 2017; Pennisi 2025, among others). Discussing the traditional perspective of the functionalist diglossic continuum of the Arabic language (Youssi 1992), this study aims to compare the morphosyntactic characteristics of (Moroccan) Mixed Arabic in oral and written productions through speakers/writers practices emerging from Moroccan digital media production. While several studies have already focused on the descriptions of dialectal elements occurring in different textual typologies, especially in Moroccan traditional media (Hoogland 2013, 2018; Brigui 2016, among others), the present study aims to analyze how a (Moroccan) Mixed Arabic style contributes to (informally) conventionalize a journalistic register, which is continuously employed in online newspapers and digital multimodal platforms. In order to achieve those goals, a corpus of written and oral data from 1) a digital Moroccan newspaper (Goud), 2) episodes of a talk-show, and 3) podcast, i.e. premeditated and unpremeditated communication in written and oral communication, has been contextually analyzed. The comparative analysis of oral and written practices shows that a mixed register of contemporary (Moroccan) Mixed Arabic is spreading in formal media Moroccan communication, serving variable discursive strategies.